The Liberal Cloak: The Constant-De Pradt Controversy on Bolívar’s Last Dictatorship - Aguilar Rivera, José Antonio (Anuario de Historia de América Latina, 2018)
This paper examines the 1830 polemic between Benjamin Constant and the Abbé de Pradt over Simón Bolívar’s last dictatorship. I argue that in the debate a key flaw of liberal constitutionalism was evidenced: the lack of a theory of emergency powers. The new nations of Latin America drafted constitutions following Constant’s ideas regarding emergency provisions. Constant had argued forcibly against broad emergency provisions. While Bolívar was an admirer of Constant, he deviated from his constitutional thinking regarding temporary emergency provisions.